Response of ant functional composition to fire. Issue 11 (3rd May 2013) - Arnan, Xavier; Cerdá, Xim; Rodrigo, Anselm; Retana, Javier
Abstract : Little is known about the impact of disturbances on functional diversity and the long‐term provisioning of ecosystem services, especially in animals. In this work we analyze the effect of wildfire on the functional composition of Mediterranean ant communities. In particular, we asked whether a) fire changes functional composition (mean and dissimilarity of trait values) at the community level; and b) such fire‐induced functional modification is driven by changes in the relative abundance‐dominance of species or by a replacement of species with different traits. We sampled ant communities in burned and unburned plots along 22 sites in a western Mediterranean region, and we computed two complementary functional trait composition indices ('trait average' and 'trait dissimilarity') for 12 functional traits (related to resource exploitation, social structure and reproduction) and with two different datasets varying in the way species abundance is considered (i.e. abundance and occurrence data). Our results suggest a set of functional responses that seem to be related to direct mortality by fire as well as to indirect fire‐induced modifications in environmental conditions relevant for ants. Trait average of colony size, worker size, worker polymorphism and the ratio between queen and worker size, as well as the trait dissimilarity of the proportion of behaviorally dominant species and of liquid food consumption, and overall functional diversity, were higher in burned than in unburned areas. Interestingly, different patterns arise when comparing results from abundance and occurrence data. While the response to fire in trait averages is quite similar, in the case of trait dissimilarity, the higher values in response to fire are much more marked when considering occurrence rather than abundance data. Our results suggest that changes in trait average are driven at the same time by replacement of species with different traits and by changes in the relative abundance‐dominance of species, while fire promotes a higher diversity of functions that is primarily driven by rare species that are functionally unique. Overall, we observed major fire‐induced changes in functional composition in Mediterranean ant communities that might have relevant consequences for ecosystem processes and services.